2021
DOI: 10.3389/fvets.2021.604675
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Real-Time PCR Assay for the Rapid Detection of Virulent Streptococcus equi Subspecies zooepidemicus—An Emerging Pathogen of Swine

Abstract: Streptococcus equi subspecies zooepidemicus, a zoonotic bacterial pathogen caused a series of outbreaks with high mortality affecting swine herds in multiple locations of the USA and Canada in 2019. Further genetic analysis revealed that this agent clustered with ATCC 35246, a S. zooepidemicus strain associated with high mortality outbreaks in swine herds of China originally reported in 1977. Rapid and accurate diagnosis is absolutely critical for controlling and limiting further spread of this emerging diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We found that available research is highly human-centered, with very few species of animals considered, specifically cats, 109 cattle, 5 , 16 , 33 , 169 , 170 goats, 90 horses, 34 , 149 pigs, 45 , 77 , 85 , 92 , 95 , 119 , 146 , 165 and sheep. 60 , 145 One of the 99 bacterial pathogens reportedly identified, B. bronchiseptica , was the only organism reported in human and animal studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that available research is highly human-centered, with very few species of animals considered, specifically cats, 109 cattle, 5 , 16 , 33 , 169 , 170 goats, 90 horses, 34 , 149 pigs, 45 , 77 , 85 , 92 , 95 , 119 , 146 , 165 and sheep. 60 , 145 One of the 99 bacterial pathogens reportedly identified, B. bronchiseptica , was the only organism reported in human and animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Of the included studies, all but 3 ONT studies reported numeric values of LOD. The LOD units included bacteria, 34 , 55 cfu, 14 , 29 , 127 , 156 genes/copies/genome equivalents, 6 , 37 , 170 , 174 cumulative criterion unit, 90 femtograms, 40 , 77 , 98 nanograms, 95 picograms, 120 , 121 , 161 and organisms. 71 Although these units are highly variable, they align with the MIQE recommendation that LOD can be expressed as relevant to the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the isolation and identification of SEZ strains in other animal species provide an opportunity to examine the potential contribution of this agent in causing disease. For example, an important outbreak, caused by a SEZ clustered with ATCC 35246, inducing high mortality in swine herds, was recently reported in multiple locations in USA and Canada [ 28 ]. The SEZ strain ST236 was the dominant strain type recovered from cases of mastitis in goats and sheep in Spain, and none of the caprine and ovine isolates had been previously recovered from horses [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, molecular biology technologies have attracted much more attention for the merits of accurate, fast and easy-operation [17,18]. With advantages of high sensitivity, specificity and the nucleic acid-based molecular diagnosis, molecular biologybased methods have become the preferred option for the accurate detection of pathogens gradually [19][20][21]. As well-established nucleic acid analysis approaches, polymerase chain reaction (PCR) and isothermal nucleic acid amplification have become the mainstream for the development of pathogen detection methods [22][23][24].…”
Section: Introductionmentioning
confidence: 99%